“Softciências” : technologies for teaching - Páris, César (1999)
The Ministry of Science and Technology built up a support program, which has lead to the situation where, today, every secondary school in Portugal has a multimedia PC connected to Internet. It is enough however to provide the tools and expect that things start working by themselves. So there were some other projects, namely Sub-Program 1 ("Application and Development of Information and Communication Technologies in Education"), of program NÓNIO-Século XXI" set up by the Ministry for Education which aims at supporting the development of projects in those schools as well as promoting the introduction and generaliztion of information and communication technologies in daily school activities. Following this philosophy, CCG together with the Portuguese Physical Society, the Portuguese Chemical Society, the Portuguese Mathematical Society, Physics Department of IST, Lisbon, and Exploratory Infante D. Henrique, Coimbra, formed the SOFTCIÊNCIAS consortium. The Ministry of Education has recognized this consortium as a Competence Centre for basic sciences (Physics, Chemistry and Mathematics).